Illocution on Speech Acts of Foreign Students in Indonesian Learning - Tri Budiasih, Latifah (Master Program in Linguistics, Diponegoro University, 2016)
This research discusses illocution on speech acts of foreign students in Indonesian Language learning. Illocution is a speech that shows the state of language relating to the situation in general and aims to express something from the speaker to the partner. This research aims to describe the forms of illocution done by the Indonesian Language students. This is a qualitative study. Observation, interviews, and documentation methods are used to collect data. The data are the utterances containing illocutionary force (assertive, declaration, directives, commissive, and expressive) in learning activities. The data source in this research is the speech acts of a foreign student in Indonesian Language learning.